SAA's extension model: Scaling sustainable farming in Nigeria - Kirui, Oliver K.; Balana, Bedru; Olanrewaju, Opeyemi; Edeh, Hyacinth O.; Nwagboso, Chibuzo (International Food Policy Research Institute, 2025)
In Nigeria, scaling agricultural innovations faces a major enabling environment challenge. This includes weak national extension systems, low extension officers-farmer ratios (1:1,800–1:3,000) and ineffective input-output market linkages, limiting technology adoption, and value addition for smallholders. The Sasakawa Africa Association (SAA) addressed this through its Value-Chain Based Extension (VCBE) Models, including Commodity Association Trader-Trainers and post-harvest centers, fostering public-private partnerships to build capacity, improve group dynamics, and create aggregation hubs. This innovative extension model has mobilized agricultural produce valued at approximately USD 3.9 million and delivered significant impact for smallholder farmers. The approach has doubled maize yields—from traditional levels of 2,438 kg/ha to 4,823 kg/ha—while enhancing incomes for more than 455,200 farmers. These outcomes are strengthening both food security and economic resilience across participating communities.